Lineage specific composition of cyclin D-CDK4/CDK6-p27 complexes reveals distinct functions of CDK4, CDK6 and individual D-type cyclins in differentiating cells of embryonic origin - Bryja, V; Pacherník, J; Vondráček, J; Souček, K; Čajánek, L; Horvath, V; Holubcová, Z; Dvořák, P; Hampl, A (Cell proliferation, 2008)
OBJECTIVES: This article is to study the role of G(1)/S regulators in differentiation of pluripotent embryonic cells. MATERIALS AND METHODS: We established a P19 embryonal carcinoma cell-based experimental system, which profits from two similar differentiation protocols producing endodermal or neuroectodermal lineages. The levels, mutual interactions, activities, and localization of G(1)/S regulators were analysed with respect to growth and differentiation parameters of the cells. RESULTS AND CONCLUSIONS: We demonstrate that proliferation parameters of differentiating cells correlate with the activity and structure of cyclin A/E-CDK2 but not of cyclin D-CDK4/6-p27 complexes. In an exponentially growing P19 cell population, the cyclin D1-CDK4 complex is detected, which is replaced by cyclin D2/3-CDK4/6-p27 complex following density arrest. During endodermal differentiation kinase-inactive cyclin D2/D3-CDK4-p27 complexes are formed. Neural differentiation specifically induces cyclin D1 at the expense of cyclin D3 and results in predominant formation of cyclin D1/D2-CDK4-p27 complexes. Differentiation is accompanied by cytoplasmic accumulation of cyclin Ds and CDK4/6, which in neural cells are associated with neural outgrowths. Most phenomena found here can be reproduced in mouse embryonic stem cells. In summary, our data demonstrate (i) that individual cyclin D isoforms are utilized in cells lineage specifically, (ii) that fundamental difference in the function of CDK4 and CDK6 exists, and (iii) that cyclin D-CDK4/6 complexes function in the cytoplasm of differentiated cells. Our study unravels another level of complexity in G(1)/S transition-regulating machinery in early embryonic cells.
Keywords: cykliny; buněčný rodokmen; myši; Cell Proliferation; Protein Binding; Cell Lineage; nádorové buněčné linie; cyklin E; S fáze; Cell Line, Tumor; lidé; biologické modely; Cyclins; Cyclin A; Humans; embryonální kmenové buňky; Models, Biological; cyklin D; Mice; Animals; proliferace buněk; Intracellular Space; cyklin A; Cell Differentiation; transport proteinů; Cyclin-Dependent Kinase 6; S Phase; zvířata; cyklin-dependentní kinasa 6; vazba proteinů; Cyclin-Dependent Kinase 4; Cyclin E; Cyclin-Dependent Kinase Inhibitor p27; G1 Phase; Cyclin D; intracelulární prostor; buněčná diferenciace; Embryo, Mammalian; G1 fáze; inhibitor p27 cyklin-dependentní kinasy; cyklin-dependentní kinasa 4; embryo savčí; Embryonic Stem Cells; Protein Transport